DISCURSOS SOBRE A PREVENÇÃO DA HANSENÍASE: O QUE DIZEM CARTILHAS, CARTAZES, GUIAS E PANFLETOS? DISCOURSES ON THE PREVENTION OF LEPROSY IN EDUCATIONAL MATERIALS IN HEALTH: WHAT DO BOOKLETS, POSTERS, GUIDES AND PAMPHLETS SAY? (Revista Contexto & Saúde, 2022)
Leprosy is a serious public health problem that historically affects populations living in poor living conditions. In contemporary Brazil, leprosy is a disease that affects the poorest sections of the population. Although it is a disease that, once treated, presents significant possibilities of cure and does not present a risk of contagion; due to cultural prejudice, a situation of stigma in relation to the disease still persists. When recognized as hansenian, the individual is permeated by a set of degrading designations. Thus, we recognize prevention as a noble aspect in leprosy control, and one of the forms used is information through visual communication. With this investigation we intend to identify the discourses on the prevention of leprosy printed on posters, pamphlets, guides, booklets and ordinances produced by the Ministry of Health. For this, theoretical-methodological strategies of documentary research were used in the investigation. The documents analyzed gave evidence that in the dissemination of information on leprosy prevention, what prevails is the biomedical discourse on diagnosis, treatment and cure. The sociocultural aspects of the disease with regard to prejudice are absent or are approached timidly in the documents. Moreover, sociocultural information, such as alerting to aspects of prejudice, is not perceived. Language is clearly clinical-biomedical and there is a concern to disseminate among health professionals and patients only that leprosy has a cure.
Keywords: Health Education. Leprosy. Documental Research. Prevention.